2011
DOI: 10.1128/cvi.00201-10
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Widely Used Diagnostic Tests To Detect West Nile Virus Infections in Horses Previously Infected with St. Louis Encephalitis Virus or Dengue Virus Type 2

Abstract: Primary West Nile virus (WNV) infections can be diagnosed using a number of tests that detect infectious particles, nucleic acid, and specific IgM and/or IgG antibodies. However, serological identification of the infecting agent in secondary or subsequent flavivirus infections is problematic due to the extensive cross-reactivity of flavivirus antibodies. This is particularly difficult in the tropical Americas where multiple flaviviruses cocirculate. A study of sequential flavivirus infection in horses was unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 47 publications
2
33
0
Order By: Relevance
“…The suspensions were centrifuged at 10,000 rpm for 30 min using a refrigerated centrifuge. Based on new serological evidence provided by Ledermann et al (2011) and Patiris et al (2008), the serum samples with antibody titres higher than 20 were considered positive for the tested viruses.…”
Section: Plaque Reduction Neutralisation Test (Prnt) -mentioning
confidence: 99%
See 1 more Smart Citation
“…The suspensions were centrifuged at 10,000 rpm for 30 min using a refrigerated centrifuge. Based on new serological evidence provided by Ledermann et al (2011) and Patiris et al (2008), the serum samples with antibody titres higher than 20 were considered positive for the tested viruses.…”
Section: Plaque Reduction Neutralisation Test (Prnt) -mentioning
confidence: 99%
“…Moreover, we observed that a heterotypic immunological response can be the result of the presence of sequential infections by the same or different viruses (SLEV or WNV) (Table), most often in those animals that presented titres > 160 for both viruses or in animal infected with another antigenically related flavivirus (i.e., sample numbers 1789, 1817, 1828 and 41) (Table). Ledermann et al (2011) reported high titres of antibodies (160-1280) with considerable crossreactions and a highly heterogeneous response in more than 70% of the equines previously inoculated with SLEV and then challenged with SLEV or WNV.…”
Section: Plaque Reduction Neutralisation Test (Prnt) -mentioning
confidence: 99%
“…In a geographic area where multiple species of flaviviruses circulate, accurate identification of an infecting agent depends upon the diagnostic assay as well as the infection history and immune status of the vertebrate host [27].…”
Section: Diagnostic Methodsmentioning
confidence: 99%
“…The double antibody ELISA format was used to assess antibody specificity (Ledermann et al, 2011). The following viral antigens produced by the sucrose-acetone method were applied: DENV2, WNV and SLEV and YF antigen produced in tissue culture.…”
Section: Mab Specific Recognitionmentioning
confidence: 99%